Pathogenic Attributes of Non-Candida albicans Candida Species Revealed by SEM - Furlaneto, Márcia Cristina; Andrade, Célia Guadalupe Tardeli de Jesus; Furlaneto-Maia, Luciana; França, Emanuele Júlio Galvão de; Moralez, Alane Tatiana Pereira (IntechOpen, 2012)
None